2013
DOI: 10.1016/j.homp.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multi-centric open clinical trial of homeopathy in diabetic distal symmetric polyneuropathy

Abstract: This study suggests homeopathic medicines may be effective in managing the symptoms of DPN patients. Further studies should be controlled and include the quality of life (QOL) assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…The results of the present study were concordant with those of previous studies 31 , 32 : FPG was significantly improved 12 months after individualized homeopathic management. The improvement in HbA1c was also concomitant with an improvement in FPG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the present study were concordant with those of previous studies 31 , 32 : FPG was significantly improved 12 months after individualized homeopathic management. The improvement in HbA1c was also concomitant with an improvement in FPG.…”
Section: Discussionsupporting
confidence: 92%
“…The improvement in HbA1c was also concomitant with an improvement in FPG. The magnitude of the observed difference was less in the previous studies despite the larger sample size because only patients with good glycaemic control were included (HbA1c <8%) 32 by the eligibility criteria. The larger treatment effect that was found in those with poorer glycaemic control could be understood intuitively, as there is little room for improvement for those with good glycaemic control.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…of India, has conducted many observational studies in primary health care settings to describe and investigate homeopathic health care strategies under primary care conditions and to get data to evaluate the usefulness of the therapy (e.g. for climacteric symptoms, 28 chronic sinusitis, 29 diabetic neuropathy, 30 depression, 31 schizophrenia 32 and many other disease conditions).…”
Section: Types Of Observational Studies Cohort Studiesmentioning
confidence: 99%
“…13 Two multicenter studies have suggested a promising role for homeopathic treatment in diabetic distal symmetric polyneuropathy. 14,15 This randomized controlled trial (RCT) was the first attempt at exploring the efficacy of IHMs in individuals with PD in comparison with placebos.…”
Section: Introductionmentioning
confidence: 99%